2007
DOI: 10.1111/j.1365-3180.2007.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of multiple resistance to ACCase‐inhibiting and ALS‐inhibiting herbicides in Lolium rigidum

Abstract: Summary Herbicide resistance in Lolium rigidum is widespread across much of the agricultural land in Australia. As the incidence of herbicide resistance has increased, so has the incidence of multiple herbicide resistance. This reduces the herbicide options available for control of this weed. This study reports on the successful amplification and sequencing of the acetolactate synthase (ALS) gene of L. rigidum using primers designed from sequence information of related taxa. This enables, for the first time, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 21 publications
1
41
0
2
Order By: Relevance
“…For the (Patzoldt & Tranel, 2001), Gli 654 (Laplante et al, 2009), and for the sulfonylureas, replacement at position Pro 197 (Yu et al, 2008); Asp 376 (Zheng et al, 2011); Arg 377 (Massa et al, 2011). The replacement of Trp574 causes high resistance to chemical groups of sulfonylureas and imidazolinones simultaneously (Patzoldt & Tranel, 2002;Tan et al, 2007). The replacement of Ala-122-Tyr results in imidazolinone resistance, but not to sulfonylureas, while the replacement of Ala-122-Tir originates imidazolinone resistance, sulfonylureas and sulfonanilide, probably because Tir present a residue much larger and more aromatic than the Thr (Han et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…For the (Patzoldt & Tranel, 2001), Gli 654 (Laplante et al, 2009), and for the sulfonylureas, replacement at position Pro 197 (Yu et al, 2008); Asp 376 (Zheng et al, 2011); Arg 377 (Massa et al, 2011). The replacement of Trp574 causes high resistance to chemical groups of sulfonylureas and imidazolinones simultaneously (Patzoldt & Tranel, 2002;Tan et al, 2007). The replacement of Ala-122-Tyr results in imidazolinone resistance, but not to sulfonylureas, while the replacement of Ala-122-Tir originates imidazolinone resistance, sulfonylureas and sulfonanilide, probably because Tir present a residue much larger and more aromatic than the Thr (Han et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The possibility of target-site-and non-target-site-based resistance mechanisms (NTSR) within a weed population or even within a single individual have been extensively discussed in previous studies [12,23]. The probability of NTSR mechanisms, causing cross-and/or multiple resistance patterns and thus biasing the planned herbicide efficacy studies, had to be reduced for the selected genotypes.…”
Section: Ahas Genotype Selection and Purificationmentioning
confidence: 98%
“…The detection of NTSR mechanisms in selected genotypes was based on the hypotheses that NTSR results in differential susceptibility to cyclohexanediones (CHD) and aryloxyphenoxy-propionates (APP). It is assumed that plants bearing NTSR are susceptible to cycloxydim (CHD) and resistant against clodinafop (APP) [23,29]. After four multiplication steps, four tillers per parent plant were treated with clodinafop at a rate of 60 g AI ha -1 (Topik 100, 100 g AI l -1 , Syngenta Agro GmbH).…”
Section: Ahas Genotype Selection and Purificationmentioning
confidence: 99%
“…Plants resistant to chlorsulfuron were reported in previous studies. Tan et al (2007) tested some populations of Lolium rigidum and found 84-100 % of surviving plants at the dose of 15.0 g/ha. Adkins et al (1997) reported the Fallopia convolvulus (F) resistance to chlorsulfuron.…”
Section: Second Bioassaymentioning
confidence: 99%